C = 1/6 (10b-7a)
C = (1/6*10b) - (1/6*7a)
C = 5/3 b - 7/6 a
+7/6 a +7/6 a
C + 7/6 a = 5/3 b
7/6 a = 5/3 b + C
oops not done.
(7/6 a) / 7/6 = (5/3 b + C)/ 7/6
a = (5/3 b + C)*(6/7)
a = 10/7 b + 6/7 C
multiply both sides by 6
6C = 10b - 7a
7a = 10b - 6C
a = (10/7)b - (6/7)C
ALGEBRA again still need help ! - need help solving this word problem, ...
algebra - I need help solving and graphing the equation. y= -7+3
college algebra - I need help solving this equation. 3√z+1=-3 How do I do ...
algebra - I need help solving this quadratic equation. 4x^2=13x+12
algebra II - need help solving the equation 5y-14+7y-20y
Quadratic Functions - I need help solving this equation: y=-2x^+3 And you do ...
Algebra - I need help solving this equation. [SQRT(x + 3)] - [SQRT(x - 2)] =1 I ...
algebra - 48 equals a number increased by 6, and the sum, all multiplied by 5. ...
Algebra - How is solving for a specified variable in a formula similar to ...
algebra - can you help me find the roots of the polynominal of 5x^2 -x.... I ...